Correlation of Fetal Cerebroplacental Ratio with Adverse Perinatal Outcome in Clinically suspected Intrauterine Growth Restriction (Bangladesh Journal of Radiology and Imaging, 2026)
Background: Intrauterine growth restriction is defined as a fetus’s development rate being slower than normal given the fetus’s growth potential (for that particular gestational age). Intrauterine growth restriction (IUGR), as one of the primary causes of prenatal death and morbidity, has enormous ramifications for children’s short- and long-term growth. Objective: To correlate cerebroplacental ratio with adverse perinatal outcomes in intrauterine growth restriction. Materials and Methods: A total of 60 females with singleton pregnancies between 30- 40 weeks of gestation with IUGR were subjected to obstetric Doppler ultrasonogram. The MCA-PI and UA-PI were recorded, and CPR was calculated. All patients underwent serial sonographicevaluation of fetal weight and the abovementioned Doppler indices at two weeks intervals until delivery. Results: The validity of emergency CS for evaluating suspected IUGR pregnancies was correlated by CPR calculating sensitivity 84.4%, specificity 71.4%, accuracy 78.3%, positive predictive value 77.1% and negative predictive value 80.0%. The validity of low birth weight for evaluating suspected IUGR pregnancies was correlated by CPR calculating sensitivity 89.2%, specificity 91.3%, accuracy 90.0%, positive predictive value 94.3% and negative predictive value 84.0%. The validity of low APGAR score for evaluating suspected IUGR pregnancies was correlated by CPR calculating sensitivity 90.6%, specificity 100%, accuracy 94.4%, positive predictive value 100% and negative predictive value 88.0%. The validity of NICU admission for evaluating suspected IUGR pregnancies was correlated by CPR calculating sensitivity 89.5%, specificity 56.1%, accuracy 66.7%, positive predictive value 48.6% and negative predictive value 92.0%.Conclusion: A better indicator of poor prenatal outcomes would be cerebroplacental ratio (CPR) measurement and Doppler evaluation, which are non-invasive tools for clinical practice. Cerebroplacental ratio should be taken into consideration as a sign of placental underperfusion and placental reserve and may prove to be a valuable indicator to pinpoint fetuses that are more likely to experience hemodynamic disturbances prior to delivery.